The Influence of Index Card Match Learning Models on Motivation And Learning Outcomes in Class V IPS Lesson / Pengaruh Model Pembelajaran Index Card Match terhadap Motivasi dan Hasil Belajar pada Pelajaran IPS Kelas V - siti nazariah (Al-Mudarris: Journal Of Education, 2020)
The convesional model that was previously applied in class V MIN 33 Aceh Besar so that it makes students less active in participating in social studies learning schingga change the pattern by applying the Index Crad Macth learning model. This study aims to explain the effect of the application of the Index Card Match learning model on student motivation and learning outcomes in the social studies subject for class class V MIN 33 Aceh Besar. The type of this research is qualitative based on facts or events systematically and accurately. The data collection technique was carried out by interviewing respondents namely 2 (two) Social Studies teachers in Class V and 1 (one) informant, namely the Principal at MIN 33 Aceh Besar. The results showed that the application of learning methods with the Index Card Match system could increase student motivation in social studies subjects in class V MIN 33 Aceh Besar, this can be seen from the higher level of student activity. The final score show that the learning outcomes of students also increase, this is can be seen from the point of value, creativity, cognitive, affective and psyhological abilities that achieve KKM completeness with a mean value of this study is that the Index Card Match learning model has an effect on the motivation and learning outcomes of students in sosial studies.